An economically viable removal of methylene blue by adsorption on activated carbon prepared from rice husk - Sharma Y.C.; Uma; Upadhyay S.N. (My University, 2025)
Application of an agricultural waste material, rice husk, has been investigated for preparation of activated carbon. The rice husk-activated carbon (RHAC) was successfully utilised for the removal of a cationic dye, methylene blue (MB) from aqueous solutions. The activated carbon was prepared in presence of ZnCl2 as an activating agent under inert nitrogen atmosphere. RHAC was characterised for surface area, pore structural parameters, and point zero charge (pHZPC). The activated carbon was further characterised by Fourier transformation infrared (FT-IR) spectrometer, X-ray diffractometer (XRD), and scanning electron microscope (SEM). The effect of different parameters such as contact time and initial concentration, adsorbent dose, and temperature on removal of the dye from aqueous solutions was investigated. The experimental data fitted well in both the Freundlich and Langmuir isotherm models. The maximum adsorption capacity for MB was found to be 9.73mgg-1 at 303K. During the study of effect of adsorbent dose, almost a 100% removal was achieved at a higher dose of RHAC. Most of the experiments were carried out at an initial concentration of MB of 60mg/L and at 303K. Different thermodynamic parameters, viz., changes in free energy (G°), enthalpy (H°), and entropy (S°) have also been determined to explain feasibility of the process of removal. The sorption of MB on RHAC was found to be feasible, spontaneous, and endothermic in nature. © 2010 Canadian Society for Chemical Engineering.